How Entry into Parenthood Shapes Gender Role Attitudes: New Evidence from Longitudinal UK Data - Elena Grinza; Francesco Devicienti; Mariacristina Rossi; Davide Vannoni (Institute of Labor Economics (IZA), 2017)
Attitudes of women and men about how paid and unpaid work should be divided in the couple largely determine women's earnings and career prospects. Hence, it is important to understand how people's gender role attitudes are formed and evolve over the lifetime. In this paper, we concentrate on one of the most path-breaking events in life: becoming a parent. Using longitudinal panel data for the UK, we first show that, in general, entry into parenthood significantly shifts women's attitudes toward more conservative views, while leaving men unaffected. We also show that the impact on women emerges only after some time from the childbirth, suggesting that attitudes change relatively slowly over time and do not react immediately after becoming a parent. Finally, we show that the impact gets large and strongly significant for women and men whose prenatal attitudes were progressive. In particular, we find that the change in attitudes for such individuals increases as the postnatal arrangements are more likely to be traditional. Overall, these findings suggest that the change in attitudes is mainly driven by the emergence of a cognitive dissonance. Broad policy implications are drawn.
Keywords: J16; J13; 330; gender equality; gender role attitudes; entry into parenthood; cognitive dissonance; changes in the hormonal production; Understanding Society (US) data set